Aleksei Prokopenko. Messengers of the Kingdom: The theology of Old Testament prophets. - Yakim, Vladimir (Bogoslovskie razmyšlenija, 2018)
Book reviwe: Vestniki Tsarstva: Bogoslovie vetkhozavetnykh prorokov. [Messengers of the Kingdom: The theology of Old Testament prophets]. By Aleksei Prokopenko. Tver’: TPK, 2015. Pp. 411. ISBN 978-5-9905130-8-2; 150.00 UAH.